Taste, consumption, and markets : an interdisciplinary volume - Arsel, Zeynep; Bean, Jonathan Y. (Routledge interpretive marketing research series., 2018)
"Taste is a core concept for the social sciences and an orienting notion in everyday practice. It is of equal relevance to academics and laypeople alike. Theorizations of taste are frequently multi- disciplinary, bringing an opportunity to cross-fertilize ideas and concepts. At the same time, a reader, challenged by the diverse body and dispersed nature of theories on taste, needs guidance navigating the literature and framing areas of interest. Until now, those interested in an academic perspective on the concept have had to traverse a wide range of literature. This is the first book that assembles a range of writings on taste from across disciplines to provide the reader with a sense of the emerging and expanding boundaries of this field of study. Taste, Consumption and Markets offers a comprehensive and up-to-date review of taste, with an emphasis on how taste shapes boundaries, subcultures, and global culture, complemented by an introduction that provides a scaffold for the reader and a concluding section that reflects on the past, present, and future of research on taste. It shows the latest state of knowledge on the topic and will be of interest to students at an advanced level, academics, and reflective practitioners. It addresses the topics with regard to the sociology of taste and consumption and will be of interest to researchers, academics, and students in the fields of consumer studies, consumption ethics, sociological perspectives on consumption, and cultural studies"--